BAHAN AJAR KESETIMBANGAN DAN DINAMIKA ROTASI DENGAN PENDEKATAN FILOSOFIS - Faikotun Nikmah; Agus Yulianto; Siti Wahyuni (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2020)
The teaching material of equilibrium and rotational dynamics in this study developed using a philosophical approach. Teaching materials compiled contain elements of ontology, epistemology, and axiology. The research conducted using the research and development method through 9 stages, namely the study of potential and problems, data collection, product design, design validation 1, revision stage 1, design validation 2, revision stage 2, limited trials, and final product. The feasibility test of teaching materials based on two expert validators and students' responses using a questionnaire. The results of the study indicate teaching materials included in the feasible category, with an average value of 80.83%. The results of students' responses agreed type, with an average of 79.41%. Thus it was concluded that the entire instructional content of equilibrium and rotational dynamics developed was suitable for use in learning.